2023
DOI: 10.1186/s40635-023-00505-7
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the inferior vena cava collapsibility from subcostal and trans-hepatic imaging using both M-mode or artificial intelligence: a prospective study on healthy volunteers

Abstract: Purpose Assessment of the inferior vena cava (IVC) respiratory variation may be clinically useful for the estimation of fluid-responsiveness and venous congestion; however, imaging from subcostal (SC, sagittal) region is not always feasible. It is unclear if coronal trans-hepatic (TH) IVC imaging provides interchangeable results. The use of artificial intelligence (AI) with automated border tracking may be helpful as part of point-of-care ultrasound but it needs validation. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Hypovolemic patients can be treated with fluid challenge therapy to increase cardiac output and optimize systemic tissue perfusion [ 37 ]. Studies have shown that the use of artificial intelligence to assess inferior vena cava variations from subcostal and trans-hepatic imaging can be used to predict fluid responsiveness [ 38 , 39 ]. We will address this shortcoming and improve it in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Hypovolemic patients can be treated with fluid challenge therapy to increase cardiac output and optimize systemic tissue perfusion [ 37 ]. Studies have shown that the use of artificial intelligence to assess inferior vena cava variations from subcostal and trans-hepatic imaging can be used to predict fluid responsiveness [ 38 , 39 ]. We will address this shortcoming and improve it in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…This could facilitate exploration into the impact of differing abdominal girth and uteroplacental circulation on maternal haemodynamics, thereby providing insight into the mechanism linking prone position and altered maternal haemodynamics. Ultrasound assessment of the inferior vena cava was beyond the scope of this study, but could be used to confirm or refute the hypothesis of prone-induced vena caval compression in future studies, using the transhepatic view [ 22 ]. Furthermore, development of the cushion, in terms of shape and consistency, could provide insight into the effect of varying degrees of vena caval compression on maternal haemodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the collapsibility of the inferior vena cava, a major conduit for deoxygenated blood returning to the heart, can be evaluated using subcostal and trans-hepatic ultrasound imaging. This assessment modality exhibits the potential for assessing the fluid status of patients with advanced HCC, warranting further investigation in this area ( Sanfilippo et al, 2023 ; Zawadka et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%